Frequency of Peripheral Intravenous Catheter Related Phlebitis and Related Risk Factors: A Prospective Study - Salma, Umma; Sarker, Mohammad Abdus Sattar; Zafrin, Nahida; Ahamed, Kazi Shamin (Journal of Medicine, 2019)
Background: Peripheral Intravenous Catheterization (PIVC) related complication is a common and significant problem in clinical practices. The aim of the study was to see the pattern of complication developed by PIVC and to find out the associated risk factors. Materials & methods: A prospective study was conducted amongst 300 patients and 420 PIVCs were observed. Results: 76 (18.09%) patients developed phlebitis and among the phlebitis patients 55.26% were grade 2 and 22.37% grade 3. Hypertonic fluid infusion and some antibiotics were found as risk factors for phlebitis. Amongst the antibiotics flucloxacilin (60%), amikacin (50%), amoxicillin + clavulanic acid were most common antibiotics responsible for development of phlebitis. Conclusions: Catheterization site and use of antibiotics and potassium chloride with associated co-morbidities are predisposing factors for phlebitis. Better insertion technique may be sought to lower the incidence of PIVC related complications. J MEDICINE JUL 2019; 20 (1) : 29-33